RADIOGRAPHY TECHNIQUE OF OSSA MANUS WITH SUSPECTED FRACTURE OF PROXIMAL PHALANG DIGITI 4 AND 5 SINISTRA IN RADIOLOGY INSTALLATION OF EFARINA HOSPITAL Pangkalan KERINCI, 2020 - Bambang Kustoyo; Veryyon Harahap; Awan Pelawi; Sabrina Suci Zasneda; Sihat Manisia Siboro; Dea Rahmayani Barus (PT. Radja Intercontinental Publishing, 2021)
Radiographs of the human bones are the bones consisting of the carpal bones, the metacarpal bones and the phalanges. Fractures are broken bones, usually caused by trauma or physical exertion, the force and angle of the force, the condition of the bone itself, and the soft tissue around the bone will determine whether the fracture is complete or incomplete. A complete fracture occurs when the entire bone is broken, whereas an incomplete fracture does not involve the entire thickness of the bone. The occurrence of fractures caused by traffic accidents. The purpose of this study was to determine the procedures for carrying out radiography of the human oss with suspected fracture at Efarina Pangkalan Kerinci Hospital. The type of research used was descriptive with data collection techniques by means of observation, documentation and interviews. The results of the examination of the human oss in fracture cases at Efarina Pangkala Kerinci Hospital are generally using postero-anterior and oblique projections. The ideal x-ray machine for ossa manus radiography is a portable x-ray unit or a mobile x-ray unit with relatively low capabilities. The x-ray film used is a high speed type combined with a fast screen intensifying (IS) where this type of film and intensifying screen (IS) can produce images with good detail and sharpness. Thus the radiation dose can also be reduced for the patient and the operator himself. The x-ray film washing process used should preferably use automatic processing. It is hoped that it can be used as a reference for radiographic results, especially in fracture cases.